Effect of a Simulated Mine Rescue on Physiological Variables and Heat Strain of Mine Rescue Workers. Issue 3 (March 2019) - Konrad, Justin; Gagnon, Dominique; Serresse, Olivier; Oddson, Bruce; Leduc, Caleb; Dorman, Sandra C.
Abstract : Objective: To describe physiological responses of mine rescuers during a simulated mine emergency. Methods: Body-worn monitors ( n  = 74) and core temperature ( T c ) capsules ( n  = 54) assessed heart rate (HR), respiration rate (RR), energy expenditure (EE), oxygen consumption ( ), T c and skin temperature ( T skin ), by team position and task. A multivariate analysis was performed with team positions, tasks, and measures as factors. Results: HRmean and HRpeak were 78.6% and 94.5%, respectively, of predicted maximum heart rate. Arduous labor tasks elicited higher HR, RR, and than casualty care. Captains exhibited lower HRmean, HRpeak, RR, RRpeak, , T c, and T skin compared with other positions. T c mean exceeded 38.6 °C ( n  = 14 recorded T c >39 °C). Conclusions: Captains' physical loading and heat stress were lowest. Nonetheless, all tasks and positions induced high physical load and heat strain. Abstract : Supplemental Digital Content is available in the text